The Role of Teachers in Developing Student Character in the Digital Age - Lubis, Esa Fakhriyah; Hidayah, Hasfi Fiqri; Adelia, Nabila; Nasution, Abdul Fattah (Pusdikra-Publishing.com, 2024)
In the rapidly evolving digital era, technology has profoundly transformed various aspects of human life, including education. The advancements in information and communication technology (ICT) have created new opportunities and complex challenges, especially in shaping the character of the younger generation. Teachers now play a pivotal role not only in imparting academic knowledge but also in guiding students to become responsible individuals with strong moral values, ready to face the increasingly complex global challenges. This article emphasizes the critical role of educators in fostering students' character development amidst digital advancements. It discusses the integration of digital ethics education, promotion of soft skills, appreciation of diversity, and media literacy. Through a descriptive analysis approach, the article draws on literature and primary sources to provide practical insights for educators in navigating the intersection of education, technology, and social change.